Optimizing Zakat and Waqf through Sharia-Based Digital Platforms - Akil, Atifah Maharani; Lestari, Ayu; Ananda, Dwi; Hastuty, Ade (Jurnal Iqtisaduna, 2025)
Zakat and waqf are important instruments in the Islamic economy that serve as a source of social funding. Digitalization provides an excellent opportunity to improve accessibility, transparency, and efficiency in their management. This article examines the implementation, challenges, and optimization strategies of digital zakat and waqf in Indonesia through a literature study of journals, official reports, and international case studies. The results show that although digitalization brings significant benefits, challenges such as low digital literacy, data security, non-comprehensive regulations, and lack of trust in digital institutions are still the main obstacles. To overcome this, public education, sharia certification, strengthening digital infrastructure, and adopting best practices from other countries are needed. The findings are expected to inform policymaking and develop safe, inclusive, and sustainable digital zakat and waqf practices in Indonesia